2001
DOI: 10.1089/107999001753238060
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 and Antioxidant Activity in Interleukin-6 Knockout Mice After Induction of the Acute-Phase Response

Abstract: Hepatic cytochrome P450 (CYP) expression and antioxidant activity have been shown to decrease following endotoxin (lipopolysaccharide [LPS]) or proinflammatory cytokine administration. Using mice deficient in interleukin-6 (IL-6), the role of IL-6 in the regulation of hepatic CYP activity, glutathione (GSH) metabolism, and catalase (CAT) activity was analyzed after LPS administration. Administration of LPS produced comparable decreases in hepatic CYP3A activity in WT B6x129 (WT) mice and IL-6 knockout mice. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
17
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 34 publications
3
17
1
Order By: Relevance
“…We and others have attributed the changes in P450 expression in the LPS and C. rodentium models to the production of proinflammatory cytokines associated with the innate immune response [interleukin (IL)-1b, , and tumor necrosis factor-a (TNFa)] (Siewert et al, 2000;Warren et al, 2001;Aitken et al, 2006;Xu et al, 2006;Aitken and Morgan, 2007;Nyagode et al, 2010). There is some evidence that hepatic P450 downregulation during inflammation may be at least partly mediated by modulation of nuclear receptors including peroxisome proliferator-activated receptor-a (PPARa), pregnane X receptor (PXR), constitutive androstane receptor (CAR), retinoid X receptor-a (RXRa), and farnesoid X receptor (FXR) (Beigneux et al, 2002;Teng and Piquette-Miller, 2005;Kosters et al, 2009;Gerbal-Chaloin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We and others have attributed the changes in P450 expression in the LPS and C. rodentium models to the production of proinflammatory cytokines associated with the innate immune response [interleukin (IL)-1b, , and tumor necrosis factor-a (TNFa)] (Siewert et al, 2000;Warren et al, 2001;Aitken et al, 2006;Xu et al, 2006;Aitken and Morgan, 2007;Nyagode et al, 2010). There is some evidence that hepatic P450 downregulation during inflammation may be at least partly mediated by modulation of nuclear receptors including peroxisome proliferator-activated receptor-a (PPARa), pregnane X receptor (PXR), constitutive androstane receptor (CAR), retinoid X receptor-a (RXRa), and farnesoid X receptor (FXR) (Beigneux et al, 2002;Teng and Piquette-Miller, 2005;Kosters et al, 2009;Gerbal-Chaloin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Expression of PGP, MRP2, and CYP3A are all reduced in animal livers during infection or inflammation (Morgan, 1997;Piquette-Miller et al, 1998;Tang et al, 2000;Payen et al, 2002). In vivo and in vitro studies indicate that interleukin-6 (IL-6) and other pro-inflammatory cytokines released during the inflammatory response are primarily involved in mediating this downregulation (Sukhai et al, 2000;Hartmann et al, 2001;Lee and Piquette-Miller, 2001;Warren et al, 2001). Although the molecular mechanism of this phenomenon has yet to be elucidated, it is possible that these proteins share common regulatory pathways.…”
mentioning
confidence: 99%
“…In human and animal experimental systems, we and others have demonstrated a significant decrease in hepatic P450 activity following induction of the acute phase response (APR) by the administration of bacterial endotoxin (LPS) (Shedlofsky et al, 1994(Shedlofsky et al, , 1997Sewer et al, 1996;Roe et al, 1998;Warren et al, 1999Warren et al, , 2001. Elevated levels of cytokines [e.g., tumor necrosis factor-alpha (TNF␣), interleukin-6 (IL-6), and interleukin-1␤ (IL-1␤)] have been implicated as the primary mediators of the APR and the accompanying decline in hepatic P450 expression (Heinrich et al, 1990;Schindler et al, 1990;van Deventer et al, 1990;Parmentier et al, 1993Parmentier et al, , 1997Warren et al, 1999Warren et al, , 2001. Using "knockout" mice deficient in TNF␣ or IL-6 responses, we have shown that endogenous TNF␣ and IL-6 modulate constitutive as well as LPS-induced changes in hepatic P450 expression (Warren et al, 1999(Warren et al, , 2001.…”
mentioning
confidence: 99%
“…Elevated levels of cytokines [e.g., tumor necrosis factor-alpha (TNF␣), interleukin-6 (IL-6), and interleukin-1␤ (IL-1␤)] have been implicated as the primary mediators of the APR and the accompanying decline in hepatic P450 expression (Heinrich et al, 1990;Schindler et al, 1990;van Deventer et al, 1990;Parmentier et al, 1993Parmentier et al, , 1997Warren et al, 1999Warren et al, , 2001. Using "knockout" mice deficient in TNF␣ or IL-6 responses, we have shown that endogenous TNF␣ and IL-6 modulate constitutive as well as LPS-induced changes in hepatic P450 expression (Warren et al, 1999(Warren et al, , 2001. The mechanism by which cytokines affect P450 expression is presently unknown.…”
mentioning
confidence: 99%